Family and feminism: a new perspective for the man/woman situation - Moraes, Maria Lygia Quartim de (Universidade Estadual Paulista / UNESP, 2009)
The feminism has been questioning the traditional family organization and mainly sexuality and the feminine roles. This paper points out some new points of view about the man/woman relation trying to present the necessity of finding new ways of facing it.